The Protestant ethic and the spirit of capitalism - Weber, Max, 1864-1920 (Routledge classics., 2001)
Max Weber's best-known and most controversial work, The Protestant Ethic and the Spirit of Capitalism, first published in 1904, remains to this day a powerful and fascinating read. Weber's highly accessible style is just one of many reasons for his continuing popularity. The book contends that the Protestant ethic made possible and encouraged the development of capitalism in the West. Widely considered as the most informed work ever written on the social effects of advanced capitalism, The Protestant Ethic and the Spirit of Capitalism holds its own as one of the most significant books of the twentieth century. The book is one of those rare works of scholarship which no informed citizen can afford to ignore.